To the question of the reasons for the activation of the epidemic process of Мeasles at the stage of elimination of infection and the forecast of the situation in the near and long term - T. A. Platonova; A. A. Golubkova; S. S. Smirnova (LLC "Diagnostics and Vaccines", 2021)
Introduction. Measles infection in recent years has become particularly relevant in connection with the registration of outbreaks of this disease in various territoriesof the Russian Federation and abroad.The aim of the study is to characterize the epidemic process of measles in a large industrial city in the near and long term with the use of modern mathematical modeling technologies for making new management decisions on infection control at the elimination stage.Materials and methods. The research materials were data from statistical reports of measles incidence in Yekaterinburg from 1950 to 2019 (70 years of follow-up), medical documentation of measles cases, population vaccination data (form No. 6 for 2000-2018 and outpatient maps of children under two years of age vaccinated against measles), results of screening for measles IgG ofmedical organizations, data of planned serological monitoringof population immunity to measles in «indicator» groups in the period from 2013 to 2017 and the results of mathematical modeling of measles incidence in different scenarios of its prevention.Results. Under the influence of vaccination, the epidemic process of measles in Yekaterinburg - a city with a population of 1.5million inhabitants-has undergone significant changes. During the observation period, the incidence decreased to sporadic levels, there was no indigenous measles, drifts from endemic areas had no consequences, the epidemic process was under control. However, outbreaks of 72 cases in 2016 and 90 cases in 2019 have changed our view of measles as a eradicated infection.Of the factors that led to the spread of infection in the foci, the most significant were the presence of measles-susceptible children and adults, including those previously vaccinated, mainly in the periods remote from vaccination and revaccination, defects in the clinical diagnosis of measlesin the first and subsequent cases, and violations in the organization and conduct of anti-epidemic measures. Conclusion. Based on the data of mathematical modeling of the epidemic process of measles with different combinations of its determinants, for the elimination of infection, it is necessary to ensure vaccination against measles at the age of 1 year and 6 years in 95-97.5%. In vulnerable groups for infection to discuss the introduction of routine revaccination among people up to 50 years of age with an interval of 10 years.